A study of the dynamic compressive response of AZ31/Al2O3 nanocomposites and the influence of nanoparticles. (March 2016) - Chen, Y.; Guo, Y.B.; Gupta, M.; Shim, V.P.W.
Highlights: AZ31 nanocomposites exhibit negative strain rate sensitivity. Adding nanoparticles does not generate any significant influence on the compressive ductility of monolithic AZ31. The effects of nanoparticles and strain rates on flow stress and failure strain are elicited and discussed. Abstract: The dynamic compressive mechanical behavior of AZ31-based nanocomposites is investigated for strain rates up to 2.5 × 10 3 s −1, using a split-Hopkinson pressure bar. Results indicate that when the grain size of AZ31 nanocomposites is close to 1 µm, the yield stress still follows the Hall–Petch law for quasi-static compression. The influence of strain rate on the flow stress of AZ31 nanocomposites is significant, and they exhibit negative strain rate sensitivity (SRS). This is postulated to be because the presence of nanoparticles elevates localized stress within the material when the strain rate is increased; hence, the applied stress required to activate tension twinning reduces correspondingly. The addition of nanoparticles (Al2 O3 ) does not generate any positive influence on the compressive ductility of monolithic AZ31; this contrasts with significant enhancement in ductility for tension. It is proposed that this arises from profuse tension twinning during compression.